Inflammatory myofibroblastic tumor in the retromolar region of mandible: a case report and literature review - Souza, Fabrício Tinôco Alvim de; Siqueira, Elisa Carvalho de; Trajano, Viviane Carvalho da Cunha; Lacerda, Júlio César Tanos de; Aguiar, Maria Cássia Ferreira de; Mesquita, Ricardo Alves de (Journal of Oral Diagnosis, 2017)
Inflammatory myofibroblastic tumor (IMT) is a soft tissue tumor that is most common in lungs but it can be located in a large variety of anatomical sites. The occurrence in the oral cavity is rare and exhibits a wide spectrum of clinical behavior. This article is a case report and review of the literature of oral IMT presentation. Here, we report an unusual IMT in retromolar region on the left side in a 21-year old female patient. This is the second case of IMT in this anatomic region reported in English-language literature. IMT case reports are important to better understand the clinical, histopathological and behavioural aspects of this tumor. The complete surgical excision of the tumor seems to be the effective treatment.